Determination of Chlorophyll Concentration in In Vitro Peanut Leaves - Faustinelli, Paola C. (2025)
The detection of chlorophyll is a convenient method for assessing gene editing efficiency when generating mutations in the phytoene desaturase (PDS) gene, which is related to chlorophyll biosynthesis. Various instruments and protocols are available for measuring chlorophyll; however, a minimum leaf area is required for precise quantifications. In vitro plant regeneration often requires several months to produce enough leaf tissue for chlorophyll content analysis. In this study, we optimized an existing chlorophyll quantification method by using a minimal amount of in vitro leaf tissue (<2.0 mg) and a microvolume of chlorophyll extraction solution (3 µl) to quantify chlorophyll a, chlorophyll b, and total chlorophyll concentration using a UV-Vis spectrophotometer. This method will serve as a basic protocol for evaluating gene editing efficiency by correlating degrees of albinism (pigment content) with changes in the PDS gene sequence.